A Single Dose of the Anti-Resorptive Peptide Human Calcitonin Paradoxically Augments Particle- and Endotoxin-Mediated Pro-Inflammatory Cytokine Production In Vitro - Jablonski, H.; Wedemeyer, C.; Bachmann, H. S.; Schlagkamp, M.; Bernstein, A.; Jäger, M.; Kauther, M. D. (Hormone and Metabolic Research, 2016)
The peptide hormone calcitonin (CT) is known to inhibit bone resorption and has previously been shown also to prevent particle-induced osteolysis, the leading cause of revision arthroplasty. In the present study, the influence of human CT on the initial inflammatory response to particulate wear debris or bacterial endotoxins, ultimately leading to osteoclast-mediated bone resorption, was analysed in human THP-1 macrophage-like cells. The cells were activated with either ultra-high molecular weight polyethylene (UHMWPE) particles or bacterial lipopolysaccharides (LPS) in order to simulate an osteolysis-associated inflammatory response. The cells were simultaneously treated with human CT (10−9 M). Cytokine production of tumour necrosis factor (TNF)-α was quantified on both RNA and protein levels while interleukins (IL)-1β and IL-6 were measured as secreted protein only. Stimulation of the cells with either particles or LPS led to a dose- and time-dependent increase of TNF-α mRNA production and protein secretion of TNF-α, IL-1β, and IL-6. Application of CT mostly enhanced cytokine production as elicited by UHMWPE particles while a pronounced transient inhibitory effect on LPS-induced inflammation became evident at 24 h of incubation. Human CT displayed ambivalent effects on the wear- and LPS-induced production of pro-inflammatory cytokines. Thereby, the peptide primarily upregulated particle-induced inflammation while LPS-induced cytokine secretion was temporarily attenuated in a distinct manner. It needs to be evaluated whether the pro- or anti-inflammatory action of CT contributes to its known anti-resorptive effects. Thus, the therapeutic potential of the peptide in the treatment of either particle- or endotoxin-mediated bone resorption could be determined.
Keywords: wear debris; lipopolysaccharides; inflammation; osteolysis; bone metabolism